CRITICAL, CREATIVE, DIFFERENT AND FREE THINKING IN ARTS AND SCIENCE EDUCATION ABOUT ARTS: CRITICAL, CREATIVE, DIFFERENT AND FREE THINKING IN ARTS AND SCIENCE EDUCATION ABOUT ARTS - Ekosiwi, Embun Kenyowati; Nursilah, Nursilah (International Journal of Performing Arts (IJPA), 2024)
This article explores the intricate relationship between critical thinking, creativity, difference, andintellectual freedom within the context of art education and the philosophy of art. Through aphilosophical-aesthetic approach grounded in critical reflection, this study discusses howquestioning, opposing, and challenging norms can function as both methods of critical inquiry andexpressions of creativity. It emphasizes that creativity is not confined to unconscious inspiration orchildlike spontaneity, but emerges through disciplined thought, lived experiences, and reflectiveengagement with cultural traditions. The paper highlights the role of tacit knowledge in traditionaldance, where creative acts are embedded in embodied practices and collective memory.Furthermore, it examines how dance serves as a metaphor for freedom, offering possibilities forartistic resistance and renewal beyond conventional boundaries. Art education, in this framework,is not merely the transfer of artistic skills, but a transformative space where critical consciousnessand imaginative capacities are cultivated. With the integration of the principles of difference,plurality, and independence of mind, educators and learners are encouraged to transcend binarythought structures and hierarchical traditions. The findings of this research affirm that fosteringcritical and creative thinking is essential to producing innovative and socially meaningful artisticpractices